2011
DOI: 10.4317/jced.3.e25
|View full text |Cite
|
Sign up to set email alerts
|

Dental considerations for the patient with diabetes

Abstract: Diabetes mellitus (DM) is one of the most frequent pathologies that dentists encounter, due to its high prevalence worldwide. It is diagnosed by the repeated obtaining of fasting plasma glucose levels of 126 mg/ dl or higher, or glycosylated hemoglobin of 6'5% or higher. Diabetes (especially if it is not well controlled) brings with it a greater risk of periodontal disease, which is the most frequent complication. On the other hand, the possible influence of periodontal disease on glycemic control is still not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This prevalence should be even higher in patients with diabetes because clinical and epidemiological studies have reported that patients with a long history of diabetes seem to have more periodontal tissue breakdown than age matched, non-diabetic controls ( 2 , 3 ). Severity and progression of the periodontitis is also higher in individuals with diabetes ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…This prevalence should be even higher in patients with diabetes because clinical and epidemiological studies have reported that patients with a long history of diabetes seem to have more periodontal tissue breakdown than age matched, non-diabetic controls ( 2 , 3 ). Severity and progression of the periodontitis is also higher in individuals with diabetes ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to dental treatment, a comprehensive medical history should be performed, singularly recording the type of diabetes, complications, treatment, and control status [249]; • International consensus guidelines state HbA1c levels <6.5% as the main parameter to measure and confirm an appropriate metabolic control [250]; • Pre-prandial blood glucose levels ranging between 70 and 130 mg/dL and postprandial blood glucose levels < 180 mg/dL also should be confirmed to ensure an adequate metabolic control [250];…”
mentioning
confidence: 99%